Representasi Muslimah Tangguh dalam Iklan Elzatta 'Hijab for Every You': Analisis Semiotika Roland Barthes - Qoniah Nur Wijayani; Darul Islam (Communicative : Jurnal Komunikasi dan Penyiaran Islam, 2026)
Advertising in the contemporary Muslim fashion industry has evolved beyond mere product promotion into a powerful arena for the construction of social meaning, cultural identity, and gendered representation. This study investigates how resilient Muslim women are represented in the Elzatta "Hijab for Every You" advertisement through a qualitative approach grounded in Roland Barthes' semiotic framework, which encompasses denotative meaning, connotative meaning, and myth. Guided by a constructivist paradigm, the research treats advertising media not as a neutral reflection of social reality but as an active site of meaning production. Drawing on Stuart Hall's representation theory as an interpretive lens, the analysis reveals that the advertisement systematically deconstructs prevailing societal myths particularly the assumption that the hijab restricts career advancement and that a woman's worth is contingent upon her conformity to conventional appearance standards. In their place, the advertisement constructs four interrelated forms of resilient Muslim womanhood: (1) successful and empowered Muslim women, (2) high-achieving Muslim women, (3) professional and multi-role Muslim women, and (4) Muslim women who serve and benefit others. These findings demonstrate that the hijab is strategically repositioned not as a symbol of limitation but as an integral marker of identity that harmonizes with professional success, intellectual achievement, and social contribution